Timing it right: The Measurement and Prediction of Flowering - Summerfiled, R. J. (Acta Agraria Debreceniensis, 2002)
Although the model described here was developed from research in controlled environments, there is now considerable evidence that in can be applied to a very wide range of natural environments in several species. Multi-locational trials augmented by successional sowing and, if considered necessary, supplementary illumination in the field to increase daylength, can be used to estimate the values of the model coefficients: (1) to characterize germplasm collections and so predict flowering behaviour elsewhere; (2) for interpreting and understanding crop adaptation; and (3) for genetic analysis of photoperiod sensitivity. We do not yet know whether the model has any contribution to make to the understanding of the biochemical mechanisms of photoperiod and temperature responses, but at the very least, it should provide the basis for indicating the most appropriate environmental conditions, genotypes and physiological stage of the plants most suitable for such investigations.